Hubungan Academic Hope Dengan Academic Grit Pada Siswa SMA Negeri 11 Makassar - Dhede Tazkiya Octsananda Ramli; Ahmad Razak; Andi Halima (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Academic grit is a trait or ability regarding determination, resilience and high focus in achieving long-term goals in the context of education. Individuals who have a high level of grit have high perseverance in doing something, do not give up easily, and even consider obstacles as a reference to be more persistent in achieving goals. One of the factors that influence academic grit is academic hope. This study aims to determine whether there is a relationship between academic hope and academic grit in students of SMA Negeri 11 Makassar. This study used a quantitative correlation approach. Respondents in this study were 301 students obtained using simple random sampling technique. The results showed that there was a significant relationship between academic hope and academic grit (r 0.642, p=0.000) where the higher the academic hope score, the higher the academic grit score at SMA Negeri 11 Makassar students. The implications of this study indicate the importance of students having the ability to maintain motivation and find strategies for achieving academic goals in order to increase individual persistence in the academic field. This research is expected to be a foundation for further researchers who examine similar variables.